Economic vulnerability and severity of debt problems: An analysis of the Irish EU-SILC 2008 - Helen Russell; Bertrand Maître; Christopher T. Whelan (The Economic and Social Research Institute (ESRI), 2011)
In this paper, using Ireland, where debt issues are of particular salience as a test case, we seek to understand the extent to which the measures currently employed as national indicators of poverty and social exclusion succeed in capturing over-indebtedness and, more broadly, severity of debt problems. Our analysis reveals a clear gradient with predictive ability increasing sharply as one moves from 'at risk of poverty' to consistent poverty and finally economic vulnerability indicators. In relation to debt problems, the key distinction is between the just under one in five households defined as economically vulnerable and all others. Financial exclusion, relating to access to a bank account and a credit card, was found to increase debt levels. However, such effects were modest. The impact of economic vulnerability seems to be largely a consequence of its relationship to a wide range of socio-economic attributes and circumstances. The manner in which a potential debt crisis unfolds will be shaped by the broader socio-economic structuring of life-chances. Any attempt to respond to such problems by concentrating on household behaviour or, indeed, triggering factors without taking the wider social structuring of economic vulnerability is likely to be both seriously misguided and largely ineffective.
Keywords: 330; poverty; economic vulnerability; over-indebtedness; severity of debt; financial exclusion; Private Verschuldung; Soziale Lage; Armut; Irland